Gender Equality and Social Inclusion in Technical and Vocation Education and Training - Bagale, Shiba (Journal of Training and Development, 2016)
This study is about the present scenario of Gender Equality and Social Inclusion GESI in the technical schools. This study has tried to explore the present scenario, how the schools are mainstreaming in GESI and how is GESI mainstreaming done in the schools. This study is qualitative in nature and the interview was done with three female and one male participant who have been working in the schools. The participants experience and perception is carried out in the study through the in-depth interview. The study shows that there are several improvements in the GESI field and most of the schools have GESI unit which seems good for the implementation of the policies formulated regarding the GESI. Also this study has tried to dig out the GESI barriers in the mainstreaming and implementation level in the local level. Though there are many changes, many improvements, there are still chances to make it more effective and make GESI friendly environment in the school.